Grammar Translation Method: Current Practice In EFL Context - Milawati, Milawati (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
This paper reports the findings of a case study investigating Grammar Translation Method (GTM) through mother tongue, much-isolated words, and putting words together in grammar class to scaffold studentsâ€™ learning. Mixed methods, classroom observations, field-notes and videotape recording, were employed to collect the data. The data gained, then, transcribed and classified by using code. The selected data is displayed into table and analyzed descriptively. While validating data is done by crosscheckingÂ  the result of data analysis of each methods. The data is reported in regard with the result of findings and discussion to answer the research questions of this study. Findings indicate that among three types of GTM, the use of mother tongues was frequently used to give instruction.Other findings show that much-isolated words were used to introduce new vocabulary, and putting words together were used to explain topic discussion. Some changes to create effective GTM through other types of GTM was also discussed.